Campylobacter hepaticus, the Cause of Spotty Liver Disease in Chickens: Transmission and Routes of Infection - Phung, Canh; Vezina, Ben; Anwar, Arif; Wilson, Timothy; Scott, Peter C.; Moore, Robert J.; Van, Thi Thu Hao (Frontiers in Veterinary Science, 2020)
The epidemiology of Spotty Liver Disease (SLD) was investigated by assaying 1840 samples collected from layer chickens and the environment in poultry farms across Australia for the presence of Campylobacter hepaticus, the agent responsible SLD in chickens. A C. hepaticus specific PCR and bacterial culture were used. Results showed that birds could be infected with C. hepaticus up to 8 weeks before clinical SLD was manifested. In addition, birds could be infected long before laying starts, as young as 12 weeks old, but the peak period for SLD outbreaks was when the birds were 26-27 weeks old. C. hepaticus DNA was detected in motile organisms such as wild birds and rats and so these organisms may be vectors for C. hepaticus dissemination. Moreover, water, soil, mites, flies and dust samples from SLD infected farms were also found to be PCR-positive for C. hepaticus DNA. However, it still remains to be determined whether these environmental sources carry any viable C. hepaticus. The indications from this study are that environmental sources are a likely transmission source of C. hepaticus. Therefore, biosecurity practices need to be strictly followed to prevent the spread of SLD amongst and between flocks. Also, a rapid, molecular detection method such as PCR should be used as to monitor for C. hepaticus presence in flocks before clinical disease is apparent, and therefore inform the use of biosecurity and therapeutic measures to help prevent SLD outbreaks.